All-wurtzite ZnO/ZnSe hetero-nanohelix: formation, mechanics and luminescence1. Issue 16 (28th April 2015) - Sun, Luwei; Ye, Zhizhen; He, Haiping
<x xml:space="preserve">Abstract</x> A unique all-wurtzite ZnO/ZnSe hetero-nanohelix is formed via growing wurtzite ZnSe nanoteeth on ZnO nanobelts through a one step thermal evaporation method.